Extent and Causes of Deviant Behaviour in the Rural Youth (Archives of Criminology, 1986)
In the years 1978-1979, a study of the extent and causes of deviant behaviour in older schoolchildren was carried out in Warsaw which included three thousand persons. boys and girls. Since there was a lack of comprehensive studies of the extent and causes of social maladjustment of the rural, youth in Poland' it was decided that this study should be repeated in typically agricultural regions. The study, carried out in late l981, was aimed at the following: to construct a Polish version of the self-report delinquency scale, to estimate the extent of deviant behaviour in the analyzed populations, and to determine the variables particularly closely related to deviant behaviour.The stratified random sample consisted of 2,144 persons (1,7O2 boys and 429 girls). They were students of 86 different grades of various secondary schools, and were aged 14- 19. The study was carried out by an anonymous questionnaire which contained 124 questions; among them. there were 42 questions - about the various types of deviant behaviour, while the remaining ones concerned the separate groups of independent  variables.The data on the following groups of independent variables were collected:1. the attitudes towards the family, the past and present and future family situation, and the character of interactions within the family; 2. deviance in the environment; 3. the attitudes towards friends, the character of interactions with friends and the intensity of bonds with the reference groups; 4. the attitudes towards school and the learning progress; 5. attitudes towards the legal norms; 6. the appraisal of life prospects and of the chances for fulfilment of aims and aspirations by means of legitimate methods; 7. the system of values, outlook on life and attitude towards moral norms; 8. engagement in social, cultural and sports activities and the like. A distinct  group were the so-called alcohol variables, analyzed separately and the socio-demographic variables. Moreover, the questionnaire contained a ninc-question lye scale.The dependent variable was an index of 42 questions about various types of deviant behaviour. The possible answers to all the questions were indentical: "never", "once or twice", "several times", "a dozen or more times" and "more often". The sum of the respondents' affirmative answers to the questions about deviant behaviour formed the so-called variety scale. The frequency scale resulted from summing up all types of answers to each of the questions. Since the correlation between the scales of variety and frequency exceeded r :0.90, the variety scale was used in the analysis. This was due to its simplicity and a greater easiness of statistical interpretation.Three groups of deviant behaviour were distinguished for the purposes of the analysis. The first of them were manifestations of behaviour given a working term of insubordination. Though not forbidden by the law, such behaviour is improper in consideration of age or represents a challenge to the authority of the parents" guardians. teachers etc. For instance. the following types of behaviour were included here: staying away from home all night without the parents' consent. running away from home, or smoking before the age of 14. The second group were acts of "dishonesty" also not penalized as a rule– e.g. failure to give a lost thing back to its owner, or steadling rides. The third and most important group were acts that bore the character of transgressions or offences. Among others, this category included brawls. beatings and other offences against person. robbery thefts. breaking and entering, receiving stolen property, and other offences against property.The examined young persons committed the following acts, most frequently: smoking before the age of 14. stealing rides. failure to give the change left from shopping back-to the parents (over 80f of affirmative answers), failure to give the change back to a shopkeeper, failure to give back a found object (over 70% of affirmatie answers). misdemeanour at school. beating. participation in a brawl (over 50% of affirmative answers). Most seldom they admited taking drugs, picking public telephones and slipping out of a pub without paying the bill (less than 10%, of the examined persons). Generally, about 35% of the examined boys (i.e. 583 persons) admitted having committed at least once a half of the, 42 acts included in the questionnaire. over 20% of boys had a high, and 7.7% a Very high level of deviance. In the Warsaw study. a very high level of deviance was found in 6.1%, of boys. Therefore, the percentage of boys with a high level of deviance is similar in both studies and nearing other Polish estimates of the extent of social maladjustment of the school youth.In the present study, hypotheses were verified which were derived from some of the most popular theories of deviance: i.a., Sutherland's theory of differential associations, Hirschi's control theory, Merton's aims – means theory, (and the related conceptions of Cloward and Ohlin), Sykes and Matza's theory of neutralization. Also certain hypotheses were verified indirectly that were derived from the Gluecks' multifactor conception and the labeling theory: The major findings were as follows:Family situationFour items of the questionnaire made together the scale of ties with the family. These were the following questions: "Do your parents try to understand your problems?'', "Do your parents trust you?,  ,,Do you generally like to discuss your plans with your parents?", "Do you trust your parents?". The scale of family ties revealed a rather high negative correlation with the deviance scale (r = -0.34 for boys and. R = -0.28 for girls). It appeared that the lesser the sense of ties with the parents. the higher the tendency to deviant behaviour. Two questions concerned the general apprasal of the atmosphere at home and the degree of the respondents' identification with their families. A strong interdependence was found between the way of defining the atmosphere- at home and the level of deviance. .The respondents who scored highest on the deviance scale, defined their atmosphere at home as bad several times more frequently, and much more seldom as good or very good, as compared with the others. As regards the question whether the respondents would like their own future families to be similar to their parental homes,  the distribution of answers was alike. Among the respondents who would not like it at all or rather would not like it, there were nearly three times more of those who scored highest on the deviance scale. The global index of the attitude towards the family (constructed with the answers to all questions concerning the ties and identification with the family) revealed a negative and rather high correlation with the deviance scale, both in the case of boys (r = -0.30) and of girls (r = -0.26). Thus it appeared that deviant behaviour is inversely related to family ties and identification. Those of the examined persons who revealed a nelative attitude towards their families scored significantly higher on the scale of deviance as compared with those whose appraisal of their homes was favourable.Deviance of the environment and attitudes towards friendsThere were four questions that concerned deviance in the environment, one of which ("Has any member of your closest family ever been convicted by the court?'') concerned the perceived intensity of deviance in the family. Both the boys and the girls whose family member had a criminal record had the highest level of deviance. This finding is of a great theoretical as well as practical value since it demonstrates the groundlessness of the frequently accepted assumption that the family is always the source of pro-social patterns of behaviour.Three questions concerned deviance of the environment, their construction aimed at reflecting various aspects of the problem both as regards the subjective and the objective point of view: the different intensity of deviance and range of environment. The questions were: "Did you ever happened to have problems at school, boarding-school or at home because of your friends?'', "Did any of your acquaintances have a case in a juveni1e court or court of general criminal jurisdiction?", "Are there many young persons in your environment who have troubles with the police?". The distribution of answers to these questions markedly differentiated the examined populations in respect to deviance. In the groups distinguished according to their level of deviance significant differences could be found as far as the deviance of the environment is concerned. The respondents whose level of deviance was the highest appeared to move significantly more often with decidedly negative circles. A scale of deviance in the environment was constructed of the above questions. Of all the scales included in the study, this one showed the highest correlation with deviant behaviour, both in the case of boys (r = 0.56) and of girls (r = 0.36).Instead, the distribution of answers to the questions about emotional ties with the reference groups, the degree of identification with these groups and the emotional stability failed to differentiate the examined populations in respect of the degree of deviance; this finding was a surprise.Attitudes towards the law There were three items in the questionnaire that concerned the attitude towards the law: "The law should be observed"; "Most of the acts people term offences actually cause no harm at all to anybody''' and "In order to get a position in life, lawless behaviour is indispensable"; the latter two were at the same time an operationalization of the Sykes and Matza's techniques of neutralization. Opinions denying or aggreeing with the statement concerning the harmlessness of offences were the 1east important in the differentiation of the examined populations in respect to the level of deviance. This variable was also least correlated with the general scale of altitudes towards the law. On the other hand, the remaining two variables of this groups did differentiate the respondents well in respect of the level of deviant behaviour. The most discriminating was the question in what situations the law should be observed. The respondents who were\of opinion that "law should always be observed irrespective of the situation'' appeared to reveal the lowest level of deviance. Instead, among the resolute legal nonconformists (,,you can break the law whenever you are certain that you will escape punishment"), those prevailed who scored highest on the deviance scale. The scale of attitudes towards the law was moderately but significantly correlated with the deviance scale, though the relationship of the presently discussed scale with that of deviance was less marked than it was the case with the scales of deviance of environmental and of the attitudes towards the family.The perceived life-chances and material situationTwo of the questions concerned the perceived life prospects that can be fulfilled by legitimate means: "what is your estimation of your life prospects as compared with those of the others?", and "Will you be able to get a good job after school?". The differences in the distributions of answers to the above questions in respect of the level of deviance were not great; however. they were significant. The "worst" respondents somewhatimore often had pessimistic, and the "best" ones - optimistic views. However, the constructed index of legitimate opportunities (which consisted of the above two questions failed to reveal a significant relation to deviant behaviour. This means that the sense of blocked opportunities for promotion and success (operationalized as above) is not related to deviant behaviour. The more so as the question about the respondents' estimation of their family material standing - though it differentiated the answers in respect of the level of deviance - also revealed a very small correlation with the scale of deviance (about 0.10).Perception of life prospects and opportunities was also analyzed from a somewhat different point of view. Namely, the respondents were asked whether in their opinion connections were necessary to get a god job. and whether it was possible to succeed in life through good honest work. These questions composed the variable "illegitimate opportunities". Constructed so as to make it complementary in relation to the variable "legitimate opportunities". An attempt was also made to ascertain to what degree this variable was correlated with the attitude towards the law. The questions about the chances of fulfilment of success goals through illegitimate means differentiated the examined populations in respect of the level of deviance. The "worst" respondents stated significantly more frequently that honest work did not lead to success in life. and that connections were necessary to get a good job. It was interesting to find that the variable "illegitimate opportunities'' was moderately correlated both with the attitude towards the law and with the "legitimate opportunities''. It was a moderately good predictor of deviant behaviour since it was correlated with the deviance scale at about 0.20 for boys as well as for girls.Values, moral principles and outlook on lifeValues treasured most frequently (love, friendship. happy home - over 75% (of all choices) failed to differentiate the examined populations in respect of their deviance. Of the remaining ten values, deep religious faith was chosen most frequently by the "best'' respondents, and acquiring individuality as well as learning to "be oneself' - by the ,,worst'' ones.The question about the stability of moral principles (three "types" of morality were distinguished: strict, situational and nihilistic) completely failed to differentiate the group of respondents Separated according to their Scores on the scale of deviance. There were among the moral nihilist as many of the "worst" as of the "best" respondents.The possible answers concerning the attitude towards religion ranged from: "I 'm a decided adherent of secular views" to: "I'm deeply religious". Generally speaking. This question provided but a poor differentiation in respect of the level of deviance. Since nearly 90%  of the examined persons were at least "not-Church-going believers". Those of the examined persons who were deeply religious were an exception. In this group, the level of deviance of this group was decidedly the lowest.Involvement in conventional activitiesOf the three questions about activities consistent with the norms (active participation in youth organizations, hobbies, participation in organized leisure activities), none appeared to differentiate the examined group in respect of the level of deviance. Instead, the questions about school achievements ("Are you a good, bad or average student?") and about learning motivation ("What is for you the importance of being a good student?") were strongly related to deviance. The "worst" respondents much more often declared themselves to be bad students and admitted not caring about learning. At the same time, the variable of motivation was a much better predictor of deviance (r=  -0.27) than the actual learning achievements (r= -0.11).Of the considered models of deviance, the most strongly confirmed was the theory of differential associations. This may be concluded from the following premises. Firstly, the variable of "devince of the environment'' and its separate elements revealed the highest correlation with the deviance scale. The test of significance of the differences of the value of correlation coefficients justifies the rejection of the null hypothesis as to their random character. Both the question about deviance among the closest friends, and those about deviance in a broader surroundings. revealed a much stronger correlation with deviant behaviour than the remaining variables. Also the question about deviance in the family appeared relate to deviant behaviour. In the light of the results obtained, not only a deviant peer group, but also a deviance in the family seem to be conducive to deviance. The adherents of the opinion that deviance precedes deviant associations would find it difficult to argue that it was the deviance in the examined persons that led to deviance in their families. Also the way in which the variable ,, deviance of the environment" is correlated with other variables speaks against the opinion that deviance precedes deviant associations since this variable a also revealed rather high correlation with deviant attitudes, the attitude towards learning at school and towards the family. Moreover, the relationship between the  variable "deviance of environment" and ,,deviant behavior” was found to increase with age which is consistent with the known of importance of peer groups in the life of youths and their growing effect. On the other hand the result in question is difficult to interpret in the terms of alternative hypotheses: the "criminal tendencies" or ,.deviant impulses’’ should after all be constant and do not change with time. Still another finding should be mentioned here. In spite of the fact that girls generally have stronger ties with their parents as compared with boys, the correlation of the attitudes towards the family with deviant behaviour was found to be smaller in the group of girls than in the group of boys. Instead, against expectations, the deviance of the environment also revealed the highest correlation with deviant behaviour in the group of girls.Hirschi's control theory was much less confirmed by the findings of the present study. Of the four elements of bonds only the  attachment to the, parents were rather strongly supported. On the other hand, hypotheses derived from the remaining elements of Hirschi.s conception were not confirmed at all (e.g. no confirmation at all was found of Hirsci’s argument that high degree of involvement in conventional types of activity is negatively related to deviance) or confirmed but to a small extent (e.g. the relationship between the school achievements and deviance). Besides the attitudes towards the family, only the attitude towards learning at school proved to be consistent with Hirschi's theory. On the other hand, in spite o| the principal hypothesis of the control theory the most isolated respondents failed to reveal a significantly higher level of deviance. Thus the conception of a solitary deviant promoted by Hirschi appears not tanable in the light of the obtained results.To sump up, if one had to decide basing on the findings of the present study which of the discussed theories was confirmed to a greater degree, it could be concluded that the theory of  differential associations was confirmed to greater extent than Hirschi's control theory. On the other had, the results of the study do not seem to speak for Merton’s aims-means theory or the conception of differential opportunities of Cloward and Ohlin. Also some of the statements of the labelling approach failed to find confirmation.